2012
DOI: 10.2209/tdcpublication.53.59
|View full text |Cite
|
Sign up to set email alerts
|

Dental Patient Preferences and Choice in Clinical Decision-Making

Abstract: In economics, the concept of utility refers to the strength of customer preference. In health care assessment, the visual analogue scale (VAS), the standard gamble, and the time trade-off are used to measure health state utilities. These utility measurements play a key role in promoting shared decision-making in dental care. Individual preference, however, is complex and dynamic. The purpose of this study was to investigate the relationship between patient preference and educational intervention in the field o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Utility value analysis is being widely employed to find not only patient preferences when it comes to treatment choices, but also to investigate cost effectiveness of various treatment modalities through cost utility analyses 14,15 Demographic characteristics like age and gender were not associated with health utilities, which was in line with previous research. [16][17][18][19][20][21][22] Although the quality of life scores as measured by OQLQ scores were lesser for Class III, and skeletal malocclusion as compared to Class I and II, the differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 87%
“…Utility value analysis is being widely employed to find not only patient preferences when it comes to treatment choices, but also to investigate cost effectiveness of various treatment modalities through cost utility analyses 14,15 Demographic characteristics like age and gender were not associated with health utilities, which was in line with previous research. [16][17][18][19][20][21][22] Although the quality of life scores as measured by OQLQ scores were lesser for Class III, and skeletal malocclusion as compared to Class I and II, the differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 87%
“…Using a rating scale like VAS to estimate health state values is easier than other direct and indirect methods, but the theoretical basis of this method is weaker. Nevertheless, studies that have used the rating scale to assess outcomes in dentistry concluded that this measure is valid and reliable 18,20,21 . Finally, we did not include patients for the estimation of health utility.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nassani and Kay [31] measured values in relation to tooth loss, Cunningham and Hunt [32] estimated values for dento-facial deformity and Fukai et al [33] valued health states in order to compare the outcomes of an educational intervention in the field of dental health.…”
Section: Quality-adjusted Life-yearsmentioning
confidence: 99%